2009
DOI: 10.1002/app.31625
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl chloride)/metallic oxides/organically modified montmorillonite nanocomposites: Fire and smoke behavior

Abstract: Nanocomposites of poly(vinyl chloride), metallic oxides (copper, molybdenum, and zinc), and organically modified montmorillonite (O-MMT) were prepared in a melt-blending or intercalation-in-the-molten state process, and their morphology was assessed with X-ray diffraction and transmission electron microscopy. The formation of an intercalated/partially exfoliated hybrid microstructure was confirmed in every situation studied. The combustion and smoke emission properties were studied with cone calorimetry, limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…The presence of copper (II) in the smoke suppressor composition apparently does not have significant synergistic effects, since SF‐4‐2 composition did not show better results than zinc composition SF‐1‐2, but too intense greenish coloration, as it can be seen in Figure 6 and Table 5. Some greenish coloration was expected due to the presence of copper (II) in SF‐4 and SF‐5, but the authors were looking for synergistic effects observed previously in other publications 5,6 . In the future, copper (I) compounds should be tested because, despite less stable than copper (II) compounds, they have the potential to impart a less negative effect on color.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of copper (II) in the smoke suppressor composition apparently does not have significant synergistic effects, since SF‐4‐2 composition did not show better results than zinc composition SF‐1‐2, but too intense greenish coloration, as it can be seen in Figure 6 and Table 5. Some greenish coloration was expected due to the presence of copper (II) in SF‐4 and SF‐5, but the authors were looking for synergistic effects observed previously in other publications 5,6 . In the future, copper (I) compounds should be tested because, despite less stable than copper (II) compounds, they have the potential to impart a less negative effect on color.…”
Section: Resultsmentioning
confidence: 99%
“…Poly(vinyl chloride) (PVC) nanocomposites with layered silicates, especially montmorillonite, have gained increased attention in recent years due to reinforcement effects induced by inorganic filler. Improved thermal resistance, enhanced stiffness and barrier properties, as well as flame retardation have been reported [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 97%
“…The A similar trend was also found in the THR results, as shown in The emission of smoke is regarded as another important parameter in the halogen-free flame retardant polymer composites. 25 The total smoke production versus time curve is presented in Figure 6. It can be observed that the smoke emission of PP composites during the combustion process is significantly decreased compared with that of neat PP, demonstrating the smoke suppression effect of the nano-fillers.…”
Section: Combustion Behaviorsmentioning
confidence: 99%